(untitled) (Sustainability in Debate, 2023)
How people move around in large Brazilian cities reflects a process of production and appropriation of urban space. The transport system is characterised by the increasing rate of individual motorisation and the precariousness of public transport services. The general objective of this paper is to evaluate the level of road cycling in the city of Belo Horizonte/Minas Gerais/Brazil, based on the proposition and analysis of indicators to assess the degree of adequacy of urban roads for bicycle use as a transport mode. The results indicate that many of the roads in Belo Horizonte have good cycling levels. Given its topography and climate, these findings go against commonly held views that consider the municipality inappropriate for cycling as a mode of transport. In reality, Belo Horizonte has a very underused high cycling potential, especially if there were investments to expand the exclusive/preferred road infrastructure.